2012
DOI: 10.3329/dujs.v60i1.10328
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Quercetin-3-O-beta-d-glucopyranoside from the Leaves of <i>Azadirachta Indica</i> and Antimicrobial and Cytotoxic screening of the Crude Extracts

Abstract: Quercetin-3-O-beta-D-glucopyranoside was isolated from the ethylacetate soluble fraction of the ethanol extract of the fresh leaves of Azadirachta indica (Family: Meliaceae). The crude extract of hexane, ethylacetate and butanol soluble fractions of this ethanol extract were subjected to antimicrobial screening and brine shrimp lethality bioassay. The ethylacetate crude extract exhibited moderate antimicrobial activity against most of the test organisms and also showed significant cytotoxicity having LC50 0.61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 9 publications
3
14
0
2
Order By: Relevance
“….00 (d) (C-5''), 61.14 (t) (C-6''). These data were found to be consistent with those reported in the literature for 3-O-β-D-glucopyranoside (Shi et al, 2016;Islam et al, 2012 andLi et al, 2008), and compound 3 identified as 3-O-β-D-glucopyranoside.…”
Section: Stigmast-4-en-3-one (2)supporting
confidence: 81%
See 2 more Smart Citations
“….00 (d) (C-5''), 61.14 (t) (C-6''). These data were found to be consistent with those reported in the literature for 3-O-β-D-glucopyranoside (Shi et al, 2016;Islam et al, 2012 andLi et al, 2008), and compound 3 identified as 3-O-β-D-glucopyranoside.…”
Section: Stigmast-4-en-3-one (2)supporting
confidence: 81%
“…Compound 3 obtained in the form of yellow powder with a melting point 872.6 °C and completely soluble in methanol, Fluorescent under ultraviolet light at a wavelength 254 and 360 nm, indicated there is founded conjugated double bonds. Comparison of physical data and physicochemical compound3.3-O-β-D-glucopyranoside or Isoquercetin shows a very high suitability (Shi et al, 2016;Islam et al, 2012 andLi et al, 2008), thus compound 3 was identified as 3-O-β-D-glucopyranoside or Isoquercetin.…”
Section: -O-β-d-glucopyranoside (3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Dari 100 gram daun mimba kering diperoleh 18 gram ekstrak metanol. Ekstrak metanol daun mimba kemudian difraksinasi dan diperoleh fraksi etil asetat sebanyak 2 gram yang kemudian difraksinasi dan dimurnikan sehingga diperoleh isolat Q4G sebanyak 14,4 mg dan Q3G sebanyak 60,1 mg. [9][10][11][12] Dengan demikian, diketahui bahwa dari 1 kg daun mimba segar BPT Situbondo mengandung isolat Q3G sebesar 60,1 mg dan Q4G sebanyak 14,4 mg.…”
Section: Pembahasanunclassified
“…Neem seed extract signifi cantly distorted the growth curve of clinical isolates of dermatophytes, T richophyton rubrum, Trichophyton mentagrophytes and Microsporum nanum in vitro at MIC of 15ug/mL (Natarajan et al 2003 ). The ethanol and ethyl acetate neem leaf extracts inhibited the growth of clinical isolates of dermatophytes isolated from human patients (Radhika and Michael 2013 ( Islam et al 2012 ). The antibiotic kanamycin was far more potent against all the test microorganisms.…”
Section: Antimicrobial Activitymentioning
confidence: 99%